Social Change in Conflict Theory: A Descriptive Study - Arditya Prayogi (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
Conflict theory is one theory that is widely used to explain various phenomena of social change that occur in society. In its dynamics, various postulates in conflict theory are constantly evolving, such as the things behind the occurrence of conflict. This article aims to describe the phenomenon of social change in the postulates of conflict theory descriptively. The writing method in this article uses a qualitative descriptive method based on the data search method in the form of library research. From the results of the discussion, it is known that conflict itself is a necessity that will occur in people's lives to be able to change the socio-cultural conditions of the community. Conflict is a normal phenomenon and at a certain point is considered important to achieve a change.